REDUCING FUEL CONSUMPTION AND ENVIRONMENTAL POLLUTION THROUGH THE USE OF NANOMATERIAL ADDITIVES IN FUEL - Latysh, O.M. (SWorld-Ger Conference proceedings, 2025)
Alternative fuels are attracting a lot of attention. Renewable energy sources, including biofuels, fuel cells, and solar technologies, make it possible to reduce fossil fuel consumption and control greenhouse gas emissions into the atmosphere